Power endurance testing in alpine ski racing - Patterson, C.; Raschner, C.; Platzer, H.-P.; Lembert, S. (Science and Skiing IV, 2009)
INTRODUCTION: Bosco (1997) developed a power endurance test for ski racers, suggesting that speed endurance measured with continuous jumps is the most important capacity for skiers. Bosco documented his work with Italian skiers (1994, 1997), but no subsequent published studies have used his or similar tests. This study presents an alternative power endurance test, and examines the effect of summer training on power endurance.